Efficacy of a novel non-contact corneal esthesiometer in assessing the neurotrophic status of the cornea in T1DM patients with bacterial keratitis (Ukrainian Journal of Ophthalmology, 2025)
Purpose: To develop a novel non-contact corneal esthesiometer and to determine the efficacy of this meter in assessing the neurotrophic status of the cornea in type I diabetic mellitus (T1DM) patients with bacterial keratitis.Material and Methods: We developed a novel non-contact corneal esthesiometer and determined the efficacy of this meter in assessing the neurotrophic status of the cornea based on examination of 30 T1DM patients with bacterial keratitis and 30 healthy individuals.Results: A corneal sensitivity assessment technique using our novel non-contact corneal esthesiometer was found to be non-invasive, accurate and repeatable. The use of low-temperature air jets in non-contact esthesiometry results in improved accuracy. Corneal sensitivity examination at nine specified points and calculation of mean corneal sensitivity threshold allows for a more comprehensive corneal function assessment, with account of the peripheral cornea.Conclusion: A significantly decreased corneal sensitivity was found in T1DM patients with bacterial keratitis. Our newly developed non-contact corneal esthesiometer was found to be effective in assessing the neurotrophic status of the cornea in T1DM patients with bacterial keratitis.
Keywords: algesimeter; non-contact corneal esthesiometer; diabetes mellitus; bacterial keratitis